Neuroblastic tumors and neurofibromatosis type 1: A retrospective multicenter study in Italy and systematic review of the literature - Puglisi, Federica; Soma, Rachele; Podda, Marta; Vetrella, Simona; Rabusin, Marco; Tropia, Serena; Meli, Mariaclaudia; Russo, Giovanna; Sorrentino, Stefania; Erminio, Giovanni; Pulvirenti, Alfredo; Ruggieri, Martino; et al. (Frontiers in Pediatrics, 2022)
Neuroblastic tumors(NBT) are the most common extra-cranial solid tumours of childhood. Neurofibromatosis type1(NF1) is the most common neurocutaneous disorder. The co-occurrence of NBT in the setting of NF1 has been occasionally reported. We explore the occurrence of NBT within NF1 and report its natural history, therapeutic strategies and outcomes in an Italian cohort of NF1 children and in the literature. Study [a]: retrospective analysis of questionnaire-based data[years 1979-2017] driven from the databases of the Italian Registry for Neuroblastoma(RINB) of the Italian Society of Pediatric Onco-Haematology(AIEOP); and Study [b]: systematic review on NF1/NB co-occurrence. Study [a] identified eight NBT children, 0.2%of patients registered in the RINB, fulfilling the diagnostic criteria for NF1. The primary site of NBT was abdominal in 6cases. Metastatic diffusion occurred in 3/8 children. MYCN gene testing, performed in 5 tumours, resulted non amplified. NF1 major features included: NF1 family in 4 cases, café-au-lait spots in all, freckling in 6, Lisch nodules in 3, neurofibromas in 3. Concerning the outcome, 4 children are alive and 4 died, 3for NB and 1 for a second tumor. Study [b] identified 12 patients with NF1/NB from 1966 to2017, median age at the diagnosis was 27 months(range=0-168 months). The primary site of NB was thoracic. Eight/nine NBs were metastatic. MYCN gene was amplified in the only studied case. The outcome was good for only 2 children, while eight children died of neuroblastoma, median age 49.5 months (range=2.4-174 months), with a median survival of 21.75 months after diagnosis. To our knowledge, this represents the first systematic study on the occurrence of NBT in NF1.It confirms that NB is rare in the setting of NF1[0.2% of all NBs] and even as compared to the overall frequency of malignancies in NF1[i.e., 14.7%].The median ages at diagnosis of NB in either study[a] and[b] were concordant and in line with what occurs in the NB population.In study[a] vs. study[b] the frequency of metastatic diffusion was lower, likely indicating less awareness in work-ups for malignancies in old NF1 series in the literature.Outcome was much better in study[a] vs. study[b] indicating that multidisciplinary treatment for NB is highly recommended.